Understanding customer relationship management technology adoption in small and medium‐sized enterprises. Issue 5 (2014) - Michael Newby; Thuyuyen H. Nguyen; Teresa S. Waring
<x xml:space="preserve"> Abstract </x> Purpose – The customer relationship management (CRM) technology adoption process in small‐ and medium‐sized enterprises (SMEs) is an under‐researched area and the purpose of this paper is to extend the knowledge and offer greater understanding of the CRM adoption process through an empirical study in the USA. Design/methodology/approach – In this study it is hypothesized that the likelihood of CRM technology being adopted is dependent on management characteristics, organizational characteristics and management's perception of CRM technology. To investigate the proposed model a survey of SMEs in the retail, manufacturing and services sectors was conducted in Southern California, USA. Findings – The results indicate that management characteristics significantly influence a firm's perception of CRM technology specifically innovativeness and positive attitude to CRM. Organizational characteristics such as the employee, information technology (IT) resources, a firms' innovativeness influence the likelihood that CRM technology will be adopted and the extent to which CRM technology will be implemented. Research limitations/implications – First, the industries focused on were in retail, manufacturing and services. Second, the sample was geographically specific to Southern California. Third, the sample size in this study was relatively small, although it is within the testable range. Finally, only one respondent was surveyed from each firm. Practical implications – Management regardless of gender, age or education level, must be supportive, innovative and have a positive attitude towards the new IT application, as positive perception will likely to lead to decision to adopt. In addition, there must be innovation within the organization and the firm must have the ability to absorb knowledge and to use it. There must be an availability of IT resources, both infrastructure and skills to support the change. Originality/value – The results of this study have implications for CRM adoption in SMEs. More importantly, they suggest a framework which demonstrates the necessary linkage between organizational characteristics and CRM adoption process. <ack> <x xml:space="preserve"> Acknowledgements </x> This paper is an extended version of a paper presented at the UKAIS Conference 2012. </ack>